복지지출 확대가 세대 간 형평성에 미치는 효과 분석: 세대 간 회계를 이용한 접근 - 전영준 (12608, 2012)
We study the sustainability of the current fiscal policy of Korea, and the effects of the social welfare policy expansion, which has been recently discussed among the political circles, on the government budget and the generational equity, using generatio